PENGARUH KECERDASAN INTRAPERSONAL DAN KEAKTIFAN BELAJAR MAHASISWA TERHADAP HASIL BELAJAR - Siti Qomariyah (Universitas Muhammadiyah Semarang, 2018)
AbstractThe purpose of this study is to know: (1) Which gives better results, students with high intrapersonal intelligence, moderate, or low, (2) Which gives better results, students with high learning activity, moderate, or low, (3) whether there is interaction between intrapersonal intelligence with students' learning activity toward student learning outcomes. This research is a quantitative research. Technique of collecting data by using test in the form of essay test. The population of this study is all students of Mathematics Education Studies STKIP Tunas Palapa consisting of 49 students. The sample in this research is 40 students of Mathematics Education Study Program which randomly selected from 43 students who take Geometry Analytic Space course. Instruments used to collect data is the instrument of student learning outcomes, intrapersonal intelligence questionnaire instrument and questionnaire of student learning activeness. The validity of the test instrument and questionnaire was performed by the validator, the test reliability tested by the KR-20 formula and the questionnaire reliability was tested by the Alpha formula. Prerequisite test used normality test, homogeneity test. While the hypothesis test using anava three way with unequal cells continued double comparation test.From result of analysis concluded that: (1) result of student learning intrapersonal high intelligence better with student with moderate and low intrapersonal intellegence but mahasiwa with intrapersonal intellegence have same result with student with low intrapersonal intellegence, (2) result of student learning having low learning activeness as well as students who have a lively learning activity, but students who have high learning activeness better with students who have the activity of learning medium and low, (3) students with each level of intrapersonal intelligence and liveliness learning to give the same results.Key Words: Intrapersonal Intelligence, Activity Student Learning and Learning Outcomes.